2017
DOI: 10.1089/biores.2016.0042
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Engineered Tendon for Enthesis Regeneration in a Rat Rotator Cuff Model

Abstract: Healing of rotator cuff (RC) injuries with current suture or augmented scaffold techniques fails to regenerate the enthesis and instead forms a weaker fibrovascular scar that is prone to subsequent failure. Regeneration of the enthesis is the key to improving clinical outcomes for RC injuries. We hypothesized that the utilization of our tissue-engineered tendon to repair either an acute or a chronic full-thickness supraspinatus tear would regenerate a functional enthesis and return the biomechanics of the tend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Finally, immediate repair after laceration also does not mimic the clinical scenario in which tendon tears are usually left untreated for weeks or months prior to repair. To model delayed repair, a few groups recently carried out supraspinatus tendon detachment followed by surgical repair 3–16 weeks later . Prolonged unloading resulted in tendon retraction, muscle atrophy, fatty infiltration, and fibrotic scarring.…”
Section: Rotator Cuff Injury Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, immediate repair after laceration also does not mimic the clinical scenario in which tendon tears are usually left untreated for weeks or months prior to repair. To model delayed repair, a few groups recently carried out supraspinatus tendon detachment followed by surgical repair 3–16 weeks later . Prolonged unloading resulted in tendon retraction, muscle atrophy, fatty infiltration, and fibrotic scarring.…”
Section: Rotator Cuff Injury Modelsmentioning
confidence: 99%
“…While MSCs delivered within such carriers generally showed some positive indicators of improved healing (such as improved histology, fibrocartilage deposition, or expression of enthesis markers), functional outcomes have been mixed. Although some studies reported improved mechanical properties, others observed no differences relative to carrier or suture controls by the final timepoint . An alternative strategy to direct differentiation is transduction of transcription factors that may induce a tenogenic cell fate, such as the transcription factors Scx or Mkx .…”
Section: Stem Cell‐based Therapies For Rotator Cuff Repairmentioning
confidence: 99%
See 3 more Smart Citations